Endocrine‐related adverse events associated with immune‐checkpoint inhibitors in patients with melanoma. (13th September 2019) - Kassi, Eva; Angelousi, Anna; Asonitis, Nikolaos; Diamantopoulos, Panagiotis; Anastasopoulou, Amalia; Papaxoinis, George; Kokkinos, Michalis; Giovanopoulos, Ilias; Kyriakakis, Georgios; Petychaki, Fotini; Savelli, Akrivi; Benopoulou, Olga; et al.
Abstract: Background: Immune‐checkpoint inhibitors have been shown to improve survival in melanoma patients, but can also trigger immune‐related endocrinopathies, especially hypophysitis and thyroid dysfunction. Methods: To assess the incidence and the spectrum of endocrinopathies in melanoma patients treated with immunotherapy a prospective observational study was conducted. Forty out of 339 patients, treated with immune‐checkpoint inhibitors, developed endocrinopathies. All patients had hormonal functional tests at screening (before the initiation of immunotherapy) and during follow‐up. Results: The total incidence of endocrinopathies was 11.8%, 13.4% due to anti‐PD1/PDL1, 5% due to anti‐CTLA4, and 18.5% due to sequential and/or combination treatment. Twenty‐one patients (6.2%) presented with isolated anterior hypophysitis, eleven (3.2%) with primary thyroid dysfunction and eight (2.4%) with both abnormalities. The most frequent anterior pituitary hormone deficiency was central adrenal insufficiency, followed by central hypothyroidism and hypogonadotrophic hypogonadism. None of the patients with corticotroph axis failure recovered during follow‐up. Endocrinopathies occurred after a median of 22 weeks (range: 4‐156) from treatment initiation. Of note, sequential and/or combination therapy with anti‐CTLA4 and anti‐PD1/anti‐PDL1 led to an almost threefold incidence of hypophysitis compared to either monotherapy. Only one of 120 patients receiving anti‐CTLA4 monotherapy developed primary hypothyroidism. Conclusions: Our cohort demonstrated an increased incidence of hypophysitis with anti‐PD1/anti‐PDL1 in contrast to the rarity of primary thyroid dysfunction with anti‐CTLA4 treatment. These results could be attributed to genetic/ethnic differences. Sequential treatment is, for the first time to our knowledge, reported to increase the risk of developing hypophysitis to a level as high as that of combination therapy. Abstract : A prospective observational study was conducted to assess the incidence and the spectrum of endocrinopathies in 339 melanoma patients treated with immune checkpoint inhibitors. Sequential and/or combination therapy with anti‐CTLA4 and anti‐PD1/anti‐PDL1 led to an almost threefold incidence of hypophysitis compared to either monotherapy, while only one of 120 patients receiving anti‐CTLA4 monotherapy developed primary hypothyroidism.